Mapping the potential of veld fire occurrence in the mountain regions of the South Western Cape, using GIS - Akinnusi, Olamigoke Adekunle (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.